TEKNOLOGI PENGOLAHAN BUAH JENGKOL DAN PEMASARAN BAGI MASYARAKAT DI DESA SIDO MAKMUR KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI - Merry Thressia; Mulyadi Mulyadi (LPPM Universitas Andalas, 2022)
Jengkol is a plant native to the tropics that is often found throughout Indonesia. Jengkol plants are woody shrubs with an average height of up to 20 meters and can live in the highlands and lowlands with brown and round fruit. Sido Makmur Village is one of the villages producing the best quality jengkol plants, which is well known outside the Mentawai Islands Regency, because it tastes good but does not smell. Every jengkol season in Sido Makmur Village, you will find jengkol fruit scattered on the side of the road because jengkol fruit is only consumed for daily side dishes and as a barrier to the house yard and is not utilized optimally. Seeing this condition, it is necessary to process jengkol fruit so that it is useful and efficient and can increase the income of the local community. The purpose of this activity is to provide the understanding and increase public knowledge as business actors of jengkol fruit about the procedures for its management and marketing methods using TTG (Appropriate Technology), such as; Market Place, Facebook, WhatsApp, Telegram, YouTube, and Instagram so that the results can increase people's income. In this activity, the method used is the lecture method and brainstorming by explaining and explaining training materials about the benefits of the jengkol plant and the processing procedures, as well as exchanging ideas and experiences between the resource persons and participants so that they can produce various kinds of culinary versions of jengkol fruit such as jengkol crackers, jengkol satay. , jengkol rendang, and jengkol nuggets. This activity was carried out in the Sido Makmur Village office hall, which was attended by 15 (fifteen) participants who were members of 3 (three) hamlets. The results of this activity are 1). Participants can understand the benefits of processing jengkol fruit, 2). Participants can process jengkol fruit into several types of culinary products such as jengkol crackers, jengkol satay, jengkol rendang, and jengkol nuggets, 3). Participants are inquisitive about the development of Appropriate Technology, so they can market jengkol fruit production outside the Mentawai Islands Regency, namely Padang City.